Low expression level of phosphatase and tensin homolog deleted on chromosome ten predicts poor prognosis in chronic lymphocytic leukemia. Issue 6 (1st June 2013) - Zou, Zhi-Jian; Zhang, Run; Fan, Lei; Wang, Li; Fang, Cheng; Zhang, Li-Na; Yang, Shu; Li, Yuan-Yuan; Li, Jian-Yong; Xu, Wei
Abstract: Phosphatase and tensin homolog deleted on chromosome ten (PTEN) is one of the best-studied tumor suppressor genes which can promote cell proliferation and contribute to tumorigenesis. This study aimed to investigate the PTEN mRNA (Pm) expression level in patients with chronic lymphocytic leukemia (CLL) and healthy controls, and its correlation with prognostic factors. Quantitative polymerase chain reaction (qPCR) was used to detect Pm expression. Compared to controls, patients with CLL presented a lower expression level of Pm ( p < 0.001). In univariate analysis, the expression level of Pm was significantly decreased in patients with Binet C ( p < 0.001) and higher level of β2 -microglobulin (β2 -MG) ( p = 0.036), lactate dehydrogenase (LDH) ( p = 0.019) and ZAP-70 ( p = 0.008). Higher Pm expression level was found in favorable cytogenetic aberrations ( p = 0.016) and the group without p53 aberration ( p = 0.005). Multivariate analysis showed that advanced Binet stage ( p = 0.027) and p53 aberration ( p = 0.007) were associated with a low PTEN expression level. Survival analysis showed that low expression of PTEN was associated with shorter time to first treatment (TTFT) ( p = 0.040). These results indicate that PTEN might be a new prognostic marker in patients with CLL.